Digital Da'wah and Persuasive Ethics: Synthesis of Methods and Pillars of Da'wah in the Interpretation of Al-Misbah and Al-Azhar in the Modern Era - Firdausi Nuzula (Jurnal Ilmiah Syi'ar, 2026)
This study examines digital da'wah and persuasive ethics through the synthesis of da'wah methods and pillars in Tafsir Al-Misbah (M. Quraish Shihab) and Al-Azhar (Buya Hamka) in the modern era. The main issue is the lack of ethics and morality in digital da'wah, such as hate speech and racist behavior on Indonesian social media with 212 million users. The objectives are to analyze da'wah methods (hikmah, mauidzah hasanah, mujadalah hasanah), pillars (da'i, mad'u, maddah), and persuasive ethics based on Quranic verses like QS. An-Nahl:125, Ali Imran:104, and Fussilat:33 for contemporary solutions. Qualitative method using library research and thematic maudhu'i tafsir approach with primary data from both tafsirs and secondary literature. Results indicate the Quran provides effective da'wah guidelines: good exemplars, gentle delivery without coercion, and optimal debate to avoid digital conflicts. This synthesis addresses gaps in prior research lacking focus on persuasive ethics